Utopia or Auschwitz: Germany's 1968 generation and the Holocaust - Kundnani, Hans (Crises in world politics, 2009)
Prologue: war, again -- The shadow of Auschwitz -- Revolutionary optimism -- From protest to resistance -- An abominable irrationalism -- The struggle continues -- Death trip -- A lifeline -- Peace -- New republic -- Power -- A war against the past -- The return of history -- A German way -- Epilogue: a new generation